A new species of the genus Trichopagurus de Saint Laurent, 1968 (Crustacea: Decapoda: Anomura: Paguridae) from a semi-submerged marine cave in Okinawa Island, southwestern Japan - Nakajima, Hiroki; Fujita, Yoshihisa; Osawa, Masayuki (Zootaxa, 2024)
A new hermit crab species of Paguridae, Trichopagurus spinibrachium n. sp., is described on the basis of a single male specimen collected from the anchialine environment of a semi-submerged marine cave in Okinawa Island, Ryukyu Islands, southwestern Japan. It is morphologically similar to T. macrochela Komai & Osawa, 2005 and T. tenuidactylus Komai, 2013, but differs in the shape and armature of the ocular, antennular and antennal peduncles, chelipeds, and ambulatory legs. The new species may be distinguished from all known congeners by the stronger armature of the carpi and meri of both chelipeds. Trichopagurus spinibrachium n. sp. is the third species of the genus recorded from submarine caves, although it may also occur on nearby coral reefs as does T. macrochela and T. trichophthalmus (Forest, 1954).